Communicating economic evidence about immigration changes attitudes and policy preferences - Allen, W; Ahlstrom-Vij, K; Rolfe, H; Runge, J (SAGE Publications, 2023)
Existing studies demonstrate that threat perceptions matter for immigration attitudes. However, while these perceptions are potentially sensitive to information about immigrants’ impacts, questions remain about whether inserting such information into public debates changes attitudes and policy preferences—especially on polarizing issues like immigration. Moreover, few studies have considered messages featuring the type of nonphotorealistic visual elements that increasingly appear in media. Using a survey experiment fielded in the United Kingdom, we examined whether evidence about European Union immigrants’ modestly positive economic impacts on the United Kingdom—presented either as text, with visualizations, or as an animated film—changed immigration attitudes and policy preferences. Although visual elements did not have an effect over and above text, all the informational treatments moved attitudes and preferences in positive directions, even among Leave voters. Our study brings together research on immigration public opinion and visual media and has implications for policymaking and journalism practice.